Ceritinib for treatment of ALK-rearranged advanced non-small-cell lung cancer. (2014) - Vansteenkiste, Johan F
ABSTRACT The anaplastic lymphoma kinase ( ALK ) gene plays a key role in the pathogenesis of selected tumors, including non-small-cell lung cancer (NSCLC). Patients with ALK -rearranged NSCLC are initially sensitive to the ALK inhibitor crizotinib but eventually become resistant, limiting its therapeutic potential. Ceritinib is an oral second-generation ALK inhibitor with greater preclinical antitumor potency than crizotinib in ALK-positive NSCLC. A Phase I trial of ceritinib in ALK-positive tumors demonstrated good activity in patients with advanced NSCLC, including those who had progressed on crizotinib. Adverse events are similar to those seen with other ALK tyrosine kinase inhibitors and are generally manageable. Ongoing trials are evaluating ceritinib in patients with ALK -rearranged NSCLC treated with prior chemotherapy and/or crizotinib.